2010
DOI: 10.1089/neu.2009.0933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Secondary Insults upon Aquaporin-4 Water Channels following Experimental Cortical Contusion in Rats

Abstract: Although secondary insults of hypoxia and hypotension (HH) are generally considered to cause fulminant brain edema in traumatic brain injury (TBI), the combined effect of TBI with HH on brain edema and specifically the expression of aquaporin-4 (AQP4) have not been fully elucidated. The goal of this study was to document the effect of secondary insults on brain water, AQP4 expression, electrolytes, and blood-brain barrier (BBB) permeability during the acute stage of edema development. We measured brain water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 39 publications
(46 reference statements)
4
47
0
Order By: Relevance
“…30,40 Importantly, these studies showed a clear correlation between the time course of the traumainduced shift in intracerebral Na + concentrations and the increase in percent brain water content. 22,30,31,39,41 Our findings were consistent with previous reports demonstrating similar shifts between water and Na + content. 31 These data provide a conceptual framework to explain the pathophysiology of cellular swelling that we demonstrate is intimately linked to trauma induced ionic dysfunction, whereas a decrease in extracellular Na + ([Na + ] e ) and a concomitant increase in K + ([K + ] e ) concentrations creates the osmotic gradient that drives water flow into the intracellular compartment, thereby setting the stage for increased brain edema and raised ICP.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…30,40 Importantly, these studies showed a clear correlation between the time course of the traumainduced shift in intracerebral Na + concentrations and the increase in percent brain water content. 22,30,31,39,41 Our findings were consistent with previous reports demonstrating similar shifts between water and Na + content. 31 These data provide a conceptual framework to explain the pathophysiology of cellular swelling that we demonstrate is intimately linked to trauma induced ionic dysfunction, whereas a decrease in extracellular Na + ([Na + ] e ) and a concomitant increase in K + ([K + ] e ) concentrations creates the osmotic gradient that drives water flow into the intracellular compartment, thereby setting the stage for increased brain edema and raised ICP.…”
Section: Introductionsupporting
confidence: 93%
“…30,40,49,50 For example, total tissue brain Na + as measured by flame photometry remained elevated at 5 h after CCI. 41 Interpreted in combination with the present ISE data showing a fall and recovery of [Na + ] e post CCI, the elevation of tissue Na + content previously reported 41 suggests that intracellular Na + must have been elevated post CCI and is likely to contribute to concomitant cytotoxic edema. Moreover, the observed extracellular K + accumulation may initiate cortical spreading depolarization (CSD), a common pathology in TBI.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These endothelial cells are further covered by astrocyte end processes and have basal lamina shared with luminal pericytes. Astrocytes express high levels of aquaporin-4, a water channel protein that is known to be involved in the clearance of edema [10,11].…”
Section: Physiologymentioning
confidence: 99%